Deletion of conserved non‐coding sequences downstream from NKX2‐1: A novel disease‐causing mechanism for benign hereditary chorea - Jun Liao; Keith A. Coffman; Joseph Locker; Quasar S. Padiath; Bruce Nmezi; Robyn A. Filipink; Jie Hu; Malini Sathanoori; Suneeta Madan‐Khetarpal; Marianne McGuire; Allison Schreiber; Rocio Moran; et al. (Molecular Genetics & Genomic Medicine, 2021)
Abstract Background Benign hereditary chorea (BHC) is an autosomal dominant disorder characterized by early‐onset non‐progressive involuntary movements. Although NKX2‐1 mutations or deletions are the cause of BHC, some BHC families do not have pathogenic alterations in the NKX2‐1 gene, indicating that mutations of non‐coding regulatory elements of NKX2‐1 may also play a role. Methods and Results By using whole‐genome microarray analysis, we identified a 117 Kb founder deletion in three apparently unrelated BHC families that were negative for NKX2‐1 sequence variants. Targeted next generation sequencing analysis confirmed the deletion and showed that it was part of a complex local genomic rearrangement. In addition, we also detected a 648 Kb de novo deletion in an isolated BHC case. Both deletions are located downstream from NKX2‐1 on chromosome 14q13.2‐q13.3 and share a 33 Kb smallest region of overlap with six previously reported cases. This region has no gene but contains multiple evolutionarily highly conserved non‐coding sequences. Conclusion We propose that the deletion of potential regulatory elements necessary for NKX2‐1 expression in this critical region is responsible for BHC phenotype in these patients, and this is a novel disease‐causing mechanism for BHC.